2022
DOI: 10.1002/pbc.29681
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine (mRNA BNT162b2) and COVID‐19 infection‐induced thrombotic thrombocytopenic purpura in adolescents

Abstract: The mRNA COVID-19 vaccine and COVID-19 infection caused by the SARS-CoV-2 virus may be immunologic triggers for the development of thrombotic thrombocytopenic purpura (TTP). There is not yet literature that discusses TTP induced by COVID-19 vaccination or infection in pediatric or adolescent patients. We describe three adolescents presenting with TTP (both de novo and relapsed disease) following administration of the Pfizer COVID-19 vaccine or after COVID-19 infection. Our observations demonstrate that the Pfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…describe three adolescents who developed thrombotic thrombocytopenic purpura (TTP) – both de novo and relapsed disease – after receiving the Pfizer COVID‐19 vaccine or after contracting COVID‐19 infection. They concluded that Pfizer‐BioNTech mRNA vaccine and COVID‐19 infection can act as triggers for both congenital and acquired TTP 1 . Both COVID‐19 infection and immunization, we agree, may induce platelet problems.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…describe three adolescents who developed thrombotic thrombocytopenic purpura (TTP) – both de novo and relapsed disease – after receiving the Pfizer COVID‐19 vaccine or after contracting COVID‐19 infection. They concluded that Pfizer‐BioNTech mRNA vaccine and COVID‐19 infection can act as triggers for both congenital and acquired TTP 1 . Both COVID‐19 infection and immunization, we agree, may induce platelet problems.…”
supporting
confidence: 50%
“…We would like to correspond and share ideas on the publication “COVID‐19 vaccine (mRNA BNT162b2) and COVID‐19 infection‐induced thrombotic thrombocytopenic purpura in adolescents.” 1 Voster et al. describe three adolescents who developed thrombotic thrombocytopenic purpura (TTP) – both de novo and relapsed disease – after receiving the Pfizer COVID‐19 vaccine or after contracting COVID‐19 infection.…”
mentioning
confidence: 99%
“…[14] Vaccines are crucial to ending the COVID-19 pandemic. [15] Thus far, the investigations on the efficacy of the COVID-19 vaccines in randomized trials [8,9] have been centered around reducing the risk of severe infection and mortality. We opine investigations on the efficacy of the COVID-19 vaccines to reduce the risk of cardiovascular outcomes should be performed to understand if COVID-19 vaccination has cardiovascular benefits.…”
Section: International Journal Of Medical Sciences and Clinicalmentioning
confidence: 99%
“…However, despite vaccines being generally safe, 1,2 there are reports of vaccine-associated immune thrombocytopenia (ITP) 3,4,5,6 and of a new entity: "vaccine induced thrombotic thrombocytopenia (VITT). 7,8 " These very rare but sometimes very serious events have received substantial media attention creating widespread apprehension about vaccine safety. 9 No published data to date have described the effects of vaccination for SARS-CoV-2 in children and AYA with preexisting ITP.…”
Section: Introductionmentioning
confidence: 99%
“…Mass vaccination against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been implemented globally for adults, teens, and now children and has effectively reduced the burden of severe disease. However, despite vaccines being generally safe, 1,2 there are reports of vaccine‐associated immune thrombocytopenia (ITP) 3,4,5,6 and of a new entity: “vaccine induced thrombotic thrombocytopenia (VITT) 7,8 9 .…”
Section: Introductionmentioning
confidence: 99%